Menilik Perkembangan Tafsir Feminis di Indonesia Ala Thomas Kuhn - Muhamad Yoga Firdaus; Suryana Alfathah; Eni Zulaiha; Edi Komarudin; Dedi Junaedi; Sholikul Hadi (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to discuss the development of feminist interpretation in Indonesia through the existence of Husein Muhammad's thoughts. This research method is qualitative through literature study with the theory of the scientific revolution initiated by Thomas Kuhn through an interpretation approach. The results and discussion of this research include a discussion of Thomas Kuhn's paradigm transition, the dynamics of feminist interpretation in Indonesia, the discourse of feminist interpretation in Indonesia according to Thomas Kuhn's paradigm transition theory, and Husein Muhammad's feminist interpretation. This study concludes that Thomas Kuhn's paradigm shift is used in interpreting feminist topics in Indonesia, which have undergone a paradigmatic transition at various levels. Tafsir Al-Qur'an Indonesia has undergone a paradigmatic transition in the classical, modern, and contemporary era. One of the commentators whose work was mapped out this time was Husein Muhammad who was in the neo-modern or contemporary era. This research is expected to have significant benefits for fans of the study of the Al-Qur'an and gender. This research only raises issues related to one feminist commentator. Then, this study recommends that in the future a more up-to-date understanding of the role of feminist commentators can be generated through a comprehensive study of western thoughts that refers to the literature on the interpretation of the Al-Qur'an in particular.